Morphometric characterization of Kacang goats raised in lowland and highland areas of Jambi Province, Indonesia (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The objective of this study was to characterize Kacang goats (aged 1–2 years) in the highland (group 1) and lowland (group 2) areas of Jambi Province based on their body measurements and body indices.  Materials and Methods: A total of 320 goats were collected from lowland (n = 160), and highland (n = 160) areas with sex proportions of 80 bucks and 80 does for each area. Eight body measurements and 12 body indices were used to characterize the Kacang goats from different areas. Results: The research showed that each animal group had one principal component (PC) for body measurements and four PCs for body indices. Thus, the body measurement of rump height (RH) and the body indices of area index, weight index, and thoracic development were suggested as the variables to distinguish the Kacang goats from different areas. However, the canonical correlation (rc) value in the study was approximately 0.30 (low). Therefore, about 59.4% (lowland) and 60.6% (highland) of Kacang goats were characterized by the body measurements, and the body indices were indicated approximately 48.8% (lowland) and 61.2% (highland) of Kacang goats. A cluster analysis of the four Kacang populations revealed that Kacang goats in this study were grouped into a first cluster (Kerinci) and a second cluster (Muaro Jambi, Batanghari, and Sungai Penuh).  Conclusion: It is concluded that body measurements and body indices cannot characterize the Kacang goats from lowland and highland areas.J. Adv. Vet. Anim. Res., 7(4): 734-743, Dec 2020http://doi.org/10.5455/javar.2020.g475